2018
DOI: 10.1111/ijlh.12907
|View full text |Cite
|
Sign up to set email alerts
|

GlycA is not a useful biomarker of inflammation in sickle cell disease

Abstract: GlycA is not a suitable biomarker of inflammation in SCD. We surmise that its signal is confounded by hemolysis leading to a depletion of haptoglobin, one of the major plasma proteins included in the composite NMR signal. Hemolysis is further exacerbated during an acute pain crisis, hence the lower GlycA levels in crisis compared to steady state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…GlycA has been shown to be a robust marker of inflammatory and proinflammatory conditions including inflammatory bowel disease, 29 gestational diabetes, 30 alcoholic liver disease, 31 cardiovascular risk, 32 rheumatoid arthritis 33 and certain cancers, 28 although GlycA is confounded by hemolysis and is not an appropriate marker of inflammatory conditions such as sickle cell disease. 34 In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies. 28 Kettunen et al reported GlycA to be predictive of mortality risk in angiography patients 31 and has also been shown to be an early predictor of subclinical cardiovascular disease and treatment response in the early stage of rheumatoid arthritis 33 and in the development of gestational diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GlycA has been shown to be a robust marker of inflammatory and proinflammatory conditions including inflammatory bowel disease, 29 gestational diabetes, 30 alcoholic liver disease, 31 cardiovascular risk, 32 rheumatoid arthritis 33 and certain cancers, 28 although GlycA is confounded by hemolysis and is not an appropriate marker of inflammatory conditions such as sickle cell disease. 34 In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies. 28 Kettunen et al reported GlycA to be predictive of mortality risk in angiography patients 31 and has also been shown to be an early predictor of subclinical cardiovascular disease and treatment response in the early stage of rheumatoid arthritis 33 and in the development of gestational diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The NMR signals for GlycA at δ 2.03 and GlycB at δ 2.07 were integrated and significant intensity differences were found between groups, with SARS-CoV-2 positive samples containing the highest median concentrations of both GlycA and GlycB, followed by SARS-CoV-2 negative samples (Figure S2). GlycA has been shown to be a robust marker of inflammatory and proinflammatory conditions including inflammatory bowel disease, gestational diabetes, alcoholic liver disease, cardiovascular risk, rheumatoid arthritis and certain cancers, although GlycA is confounded by hemolysis and is not an appropriate marker of inflammatory conditions such as sickle cell disease . In general, GlycA has been found to be a better predictor of inflammatory conditions than either C reactive protein (CRP) or interleukin-6 (IL-6), and is independent of both, although GlycA and CRP have been found to be strongly correlated in many studies .…”
Section: Resultsmentioning
confidence: 99%
“…GlycA levels are decreased in SCL. [132] Human African Trypanosomiasis Significant increase of N-acetyl glycoprotein in HAT patients. [133]…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…This result goes against what is reflected in this review and has been attributed to the fact that hemolysis is observed in SCD patients but not in patients with other pathologies. It should also be noted that haptoglobin is one of the major proteins in the GlycA signal and in this case, it depletes rapidly during intravascular hemolysis [132].…”
Section: Sickle Cell Disease (Scd)mentioning
confidence: 99%
“…Decreased GlycA in SCD has been reported before, and the plasma level of GlycA is confounded by hemolysis, thus not a suitable biomarker of inflammation in SCD. (Weisman, Meeks, Mendelsohn, Remaley, Sampson, Allen, Nichols et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%